Bio-inspired cab-roof fairing of heavy vehicles for enhancing drag reduction and driving stability. (October 2017) - Kim, Jeong Jae; Hong, Jiwoo; Lee, Sang Joon
Highlights: New types of bio-mimetic cab-roof fairings (CRFs, i.e., an air deflector mounted on the top of the cab) were devised for the drag reduction of heavy vehicles. The advanced bio-inspired CRF considerably reduced the drag coefficient of the 15-ton and 5-ton models by approximately 20% and 22.4%, respectively. The side force was also reduced by up to 8% and 9% for the 15-ton and 5-ton models at a yaw angle of ϕ = 3°, respectively. Flow characteristics (e.g., mean velocity field and turbulent kinetic energy) around the forebody of the vehicle models with and without CRFs were thoroughly analyzed by using a PIV technique to elucidate such drag-reduction mechanism. The findings provide useful information for improving the design of new forebody devices by reducing the aerodynamic drag and enhancing the driving stability of heavy vehicles. Abstract: Cab-roof fairing (CRF) has been developed to reduce the drag exerted on the forebody, thereby promoting fuel saving and environmental pollution control. Conventional CRFs with a 2D streamlined curvature have limitations in enhancing the driving stability and in reducing the drag at the forebody. In this study, new CRFs were designed with flow-guiding structures by mimicking the external forebody shape of sea lions. To evaluate the drag reduction effects of the proposed bio-inspired CRFs, three different types of CRFs (i.e., basic, bio-inspired, and advanced bio-inspired) were installed at scaled-down vehicle models of 15-ton (1:8) and 5-ton (1:6) heavy vehicles. The advanced bio-inspired CRF considerably reduced the drag coefficient of the 15-ton and 5-ton models by ∼20% and 22.4%, respectively. The side force was also reduced by up to 8% and 9% for the 15-ton and 5-ton models with the advanced bio-inspired CRF at a yaw angle of β = 3°, respectively. The flow characteristics around the forebody of the 15-ton model (1:15) with and without CRFs were analyzed by particle image velocimetry to elucidate the drag-reduction mechanism of the proposed CRFs. The bio-inspired CRFs significantly reduced the regions of separated shear flow and turbulent kinetic energy level on the side surfaces of the vehicle models. The findings provide useful information for improving the design of new forebody devices to reduce the drag and enhance the driving stability of heavy vehicles. Graphical abstract: